Contexts and Influences on the Need for Personal Flexibility for the 21st Century, Part I - Herr, Edwin L. (Canadian Journal of Counselling and Psychotherapy, 1993)
The emerging global economy has implications for both individual psychology and the structure and choice of occupations. This paper examines the growing need for personal flexibility as a response to the influence of advanced technology, new economic and political alliances, and sweeping social revolutions. The paper also addresses the central role of the counsellor in facilitating personal flexibility and in assisting persons deal with the choice and adjustment problems associated with the dynamics of a global economy.